2017
DOI: 10.1161/strokeaha.116.014322
|View full text |Cite
|
Sign up to set email alerts
|

GRECOS Project (Genotyping Recurrence Risk of Stroke)

Abstract: Background and Purpose Vascular recurrence occurs in 11% of patients during the first year after ischemic stroke (IS) or transient ischemic attack (TIA). Clinical scores do not predict the whole vascular recurrence risk, therefore we aimed to find genetic variants associated with recurrence that might improve the clinical predictive models in IS. Methods We analyzed 256 polymorphisms from 115 candidate genes in three patient cohorts comprising 4,482 IS or TIA patients. The discovery cohort was prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
18
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…In relation to stroke recurrence several studies in Asian populations [18] , [19] associations of ANRIL and NINJ2 polymorphisms with vascular recurrence. Other studies in Caucasian populations found associations between CRP and MGP polymorphisms and recurrent stroke [4] , [20] . However, other studies have not observed those associations [21] .…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…In relation to stroke recurrence several studies in Asian populations [18] , [19] associations of ANRIL and NINJ2 polymorphisms with vascular recurrence. Other studies in Caucasian populations found associations between CRP and MGP polymorphisms and recurrent stroke [4] , [20] . However, other studies have not observed those associations [21] .…”
Section: Introductionmentioning
confidence: 88%
“…The risk of ischemic stroke recurrence after a first stroke is high, especially in the early stages, being around 6–12% within the first year of the initial stroke [4] . Moreover, stroke patients also have a high risk of developing other vascular diseases such as acute myocardial infarction and vascular death.…”
Section: Introductionmentioning
confidence: 99%
“…Methylation levels of MMPs and TIMPs in plaque tissue were crossed with methylation levels in blood tissue in two new independent cohorts. Ischemic strokecohort 1 (ISC-1): 37 atherothrombotic stroke patients and 6 healthy controls, from the GRECOS study [17]; Ischemic stroke-cohort 2 (ISC-2): 80 atherothrombotic patients from the BASICMAR prospective register [18] and 184 healthy controls from REGICOR population-based cohort (Supplementary Table 2). In both cases, only atherothrombotic stroke samples were selected as defined by the Trial of Org 10172 in Acute Stroke Treatment (TOAST) [19].…”
Section: Human Whole Blood Samplesmentioning
confidence: 99%
“…Moreover, no association was found with rs1800802 or rs4236. Fernández-Cadenas and colleagues recently reported that rs1800801 associated with first-year recurrent ischemic stroke in a Spanish cohort in the Genotyping Recurrence Risk of Stroke (GRECOS) study [9].…”
Section: Plos Onementioning
confidence: 99%
“…Achterberg and colleagues did not find an additional value of genetic information in predicting recurrence of vascular events including stroke after cerebral ischemia [8]. In the Genotyping Recurrence Risk of Stroke (GRECOS) project, however, Fernándes-Cadenas et al found an association of the single nucleotide polymorphism (SNP) rs1800801 in the matrix carboxyglutamatic acid Gla protein (MGP) gene with firstyear recurrent ischemic stroke in Spanish Caucasians [9]. MGP is an extracellular matrix protein involved in the inhibition of calcification of arteries and cartilage [10].…”
Section: Introductionmentioning
confidence: 99%